THE EUROPEAN UNION AND FOOD INSECURITY AS A LOOMING THREAT (Security Dialogues, 2025)
From climate change to ethnic conflicts, from pandemics to cyber terrorism,humanity faces many non-traditional, multi-dimensional and complex security threats in the21st century. Food security is one of these challenges that concerns the whole world andrequires global solutions. The European Union (EU), as one of the actors with the highestlevel of welfare and providing the most humanitarian aid in the world, is not currently facinga serious food crisis. However, the adverse effects of climate change and the challenges thatthe Union has recently faced, such as the European debt crisis, the Covid-19 pandemic, andthe Russia-Ukraine war, have brought food security to the top of the EU agenda. This studyaims to research the issue of food insecurity in the European Union. The main argument ofthe study is that food security is not currently an acute problem for the European Union,but it is a looming threat. Although the EU has addressed food insecurity within the scopeof agricultural policy until recently, in today’s “overheated” world full of natural disasters,economic crises, wars and conflicts, food security is now requiring a multidimensionalapproach, including economic, energy, health, environmental and social policies.
Keywords: European Union, Food security, Climate change, Covid-19, Russia-Ukraine war